Strain-dependent slope stability for earthquake loading - Schmüdderich, Christoph; Machaček, Jan; Prada-Sarmiento, Luis Felipe; Staubach, Patrick; Wichtmann, Torsten (Computers and geotechnics, 2022)
Assessment of the seismic slope stability in terms of a factor of safety (FoS) is often addressed using pseudo-static approaches neglecting material-induced failure and the role of pore-fluids. On the other hand, sophisticated constitutive models that capture these effects can usually not be considered in strength reduction analyses. In this study, the concept of strain-dependent slope stability presented by Nitzsche and Herle (2020) was enhanced to enable the analysis of slope stability problems under earthquake loading. This allowed to apply advanced constitutive models to both, the dynamic and the stability analysis. The applicability of the concept was shown by analysis of FoS and failure mechanisms for a water-saturated opencast mine slope subject to earthquake loading. To capture the non-linear material behavior, the hypoplastic model with intergranular strain was used. Machine learning algorithms adopted to the problem at hand provided accurate approximations of FoS and failure mechanism while reducing computational costs by 2–3 orders of magnitude.